CONTEXTUAL TEACHING AND LEARNING BASED WRITING POETRY STUDENT WORKSHEET FOR PHASE C - Aprianti Derlis; Gusti Yarmi; tuti T adi syam (Universitas Majalengka, 2024)
Poetry writing skills are one of the Indonesian language learning outcomes in phase C. The characteristics of grade 5 elementary school students who still think concretely in writing imaginative poetry must be facilitated by contextual teaching materials. However, the student worksheets available at the research site did not meet the needs of students. This research aims to develop and test the validity of the Worksheet of Learners Writing Poetry Based on Contextual Teaching and Learning for 5th-Grade Learners. This research refers to the ADDIE development model. Data was collected using document study, interview, and questionnaire techniques. The results show that the Learner Worksheet gets an average expert validation score of 89% and is in the ‘very feasible’ category. The average score of product trials on students and teachers is 90%, with the category ‘very feasible’. Based on the results of the study, it can be concluded that the Worksheet of Learners Writing Poetry Based on Contextual Teaching and Learning is very feasible to be used in learning.